The Effect of School Principles Motivation in Efforts to Improve Teacher Performance at Integrated Islamic Elementary School - Dian, Dian; Trisna, Muhammad Yogi; Huda, Nenden Najiatul (JURNAL AL-TANZIM, 2022)
This study aimed to determine the effect of the principal's motivation on teacher performance at Integrated Islamic elementary school Matahati Bandung. The method used in this research is a quantitative approach with the associative method. The population in this study amounted to 30 teachers and was taken as a sample of 30 teachers with the research instrument in the form of a questionnaire. The result of this study; 1) the regression coefficient value is 1.006. So every one percent of motivation from the principal will improve teacher performance by 1,006. Thus the motivation of the principal has a positive effect on the teacher's performance. Square R-value = 0.610, hence the effect value is 61%. Thus, the provision of motivation from the principal can improve teacher performance by 60%; 2) the principal is significantly influential in efforts to improve teacher performance in SDIT Matahati with the magnitude of the influence by 90.6%; 3) Principals on teacher influence by 88.6%. The study results imply that the principal's motivation is a factor that can affect teacher performance.